2008
DOI: 10.1016/j.ab.2008.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Improved enrichment strategies for phosphorylated peptides on titanium dioxide using methyl esterification and pH gradient elution

Abstract: Improvements to phosphopeptide enrichment protocols employing titanium dioxide (TiO2) are described and applied to identification of phosphorylation sites on recombinant human cyclin-dependent kinase 2 (CDK2). Titanium dioxide binds phosphopeptides under acidic conditions, and they can be eluted under basic conditions. However, some nonphosphorylated peptides, particularly acidic peptides, bind and elute under these conditions as well. These nonphosphorylated peptides contribute significantly to ion suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
0
46
0
1
Order By: Relevance
“…The different aspect ratios of SPE devices and load/wash volumes may have affected the recovery and selectivity of enrichment methods. The impact of loading and eluting conditions is not fully understood [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The different aspect ratios of SPE devices and load/wash volumes may have affected the recovery and selectivity of enrichment methods. The impact of loading and eluting conditions is not fully understood [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Simon et al applied the methyl esterification on the carbocyclic-terminal of amino acid to deal with non-specific binding in titanium dioxide as it was quite efficient in IMAC and found that it also works effectively in this case. Together, they also showed the results of separation of monophosphorylated peptides and multi-phosphorylated peptides by gradient elution from pH8.5 to pH11.5 [26]. Li et al demonstrated that the ratio of loading sample amount to titanium dioxide is also an important factor for specificity of enrichment [27].…”
Section: Enrichmentmentioning
confidence: 92%
“…Using high concentration during the binding step may improve specifi city, but more weakly bound phosphopeptides could be lost, especially monophosphorylated peptides. Another approach how to minimize the level of nonspecifi cally bound peptides is chemical derivatization before the enrichment, e.g., methylesterifi cation of peptides (Ficarro et al 2002, Simon et al 2008. A variety of pH conditions during the binding or the elution step have been employed to optimize the protocol for enrichment on MOAC resins (Simon et al 2008 , Park andMaudsley 2011 ).…”
Section: Metal Oxide/hydroxide Affi Nity Chromatography (Moac)mentioning
confidence: 99%